Diversifikasi Produk Olahan Ikan Kekinian dalam rangka Pencegahan Stunting di Desa Mertak Kecamatan Pujut Kabupaten Lombok Tengah - Junaidi, Muhammad; Diniarti, Nanda; Dwiyanti, Septiana; Larasati, Chandrika Eka; Diniariwisan, Damai; Irawati, Betari Athiyah (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Potential fish resources have the opportunity to be developed as a profitable fishing business to improve the economy and nutritional quality of food. Businesses processing fishery products through diversification of processed products can not only increase benefits and added value, diversification of processed fish products can increase fish consumption which can support reducing stunting. Activities to develop diversification of contemporary processed fish products in the context of preventing stunting in the form of counseling and training will be carried out in Mertak Village, Pujut District, Central Lombok Regency. The methods used in service activities are qualitative and quantitative, where the qualitative method used is by conducting participatory observation during the education and training process. The quantitative method is carried out by distributing questionnaires in the form of questionnaires before and after attending counseling and training. Implementation of activities is carried out in three stages, namely preparation, implementation and monitoring and evaluation. The results of the activity show that the community service that has been carried out through counseling and training in the development of diversification of contemporary processed fish products, including fish nuggets and fish sempol, has been quite successful in increasing the knowledge, understanding and skills of participants, where based on pre-test and post-test evaluations the increase reached 96 -100%. Thus, this activity needs to be followed up by providing assistance to participants who have an interest in processing businesses through the formation of joint businesses, while participants who are posyandu cadres provide assistance in educating posyandu participants in the fish eating movement to prevent and reduce stunting in Mertak Village.